Psychophysical properties of odor processing can be quantitatively described by relative action potential latency patterns in mitral and tufted cells - Schaefer, Andreas T.; Margrie, Troy W. (Frontiers in Systems Neuroscience, 2012)
Electrophysiological and population imaging data in rodents show that olfactory bulb (OB) activity is profoundly modulated by the odour sampling process while behavioral experiments indicate that odour discrimination can occur within a single sniff. This paper addresses the question of whether action potential (AP) latencies occurring across the mitral and tufted cell (M/TC) population within an individual sampling cycle could account for the psychophysical properties of odour processing. To determine this we created an OB model (50 000 M/TCs) exhibiting hallmarks of published in vivo properties and used a template-matching algorithm to assess stimulus separation. Such an AP latency-based scheme showed high reproducibility and sensitivity such that odour stimuli could be reliably separated independent of concentration. As in behavioral experiments we found that very dissimilar odours (“A vs B”) were accurately and rapidly discerned while very similar odours (binary mixtures, 0.4A/0.6B vs 0.6A/0.4B) required up to 90 ms longer. As in lesion studies we find that AP latency-based representation is rather insensitive to disruption of large regions of the OB. The AP latency-based scheme described here therefore captures both temporal and psychophysical properties of olfactory processing and suggests that the onset patterns of M/TC activity in the OB represent stimulus specific features of olfactory stimuli.